Oralidade em língua estrangeira (inglês): representações discursivas - Ferreira, Edilson Pimenta (2010)
This dissertation was developed in an inter/transdisciplinary approach that involves Applied Linguistics (AL), French Discourse Analysis (DA) and Dialogical Discourse Analysis (DDA). It was designed to delineate the orality meanings constructed by subjects when they occupy the discursive place of Information Systems undergratuate, from a private university in the state of Minas Gerais in an English for Specific Purposes first term class, and, with this, investigate the constitutive representations of this orality. It was attributed to this dissertation the task to describe, analyse and delineate the representations of orality in English constructed by these computer-field undergraduate subjects; the voices raised, in polyphonic relations, by these subjects to construct the representations and evidence in which discursive formations (DFs) their discursive practices are inscribed. I studied, therefore, factors that interfere in the English language teaching process in order to better understand how these factors are translated in the relation that is instaurated between these subjects and their orality in this language. With that aim, the AREDA (Serrani-Infante, 1998) was utilized as a methodological tool for data collection. As a result, it was possible to observe that the relation that the research subjects have with their orality is ruled by four representations: i) orality as an object of desire; ii) orality as a professional upgrade; iii) orality as a legitimizer of good English command and iv) orality as the inscription of another one. These representations are interpenetrated and interconstituted and the discursive practices are circumscribed in some DFs that I classified as: DF of neoliberalism, DF of Entrepreneurship, DF of lack, DF of linguistic accuracy and DF of capacitation. While representing their orality as an object of desire, it was explicited a constant lack of nativeness, which is significant to them and makes them state that they see a nativespeaker of English as complete. While representing their orality as a professional upgrade, the DF of capacitation was explicited, as their enunciations are matched in the sense of making an effort to meet an ever-growing market demand and this way, gain respectability in a current non-stop globalization process through capacitation. The DF of Entrepreneurship and the DF of linguistic accuracy were also observed in this representation, once their desire for social mobility would only be possible through the mastering of orality and linguistic accuracy in the English language. This one reveals a structural and behavioral practice, which would also make them ascend professionally. While representing their orality as a legitimizer of good English command, it is possible to observe some meanings that characterize the DF of Entrepreneurship and the DF of neoliberalism, once the overestimation of the orality in the English language can be inscribed in a modern neoliberal capitalist mentality that would take them to the search for success circumscribed in an entrepreneurship stance. And while representing their orality as inscription of another one, the subjects project a desire for an English native-speaking condition, considered by them, as the only way for linguistic accuracy, and when this relevance is given to the native-speaker, there is a projection relation instaurated, which characterized the DF of Lack.